Effects of soluble solids inhibitor of autohydrolysed rice biomass for eradication of pomacea canaliculata species - Mohammad Hafiz Bin Mohd Zabidi (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
The biomass industry is a new breakthrough in the field of global green technology by producing several products from biomass along with the environmental conservation. The aim of this study is to investigate the feasibility of using solube solid for eradication Pomacea canaliculata by autohydrolysis biomass. P.canaliculata is the fresh water snail and live at pond, paddy field and irrigation of paddy fields. Steam pretreatment was selected to produce solube solid in order to eradicate the snail. Autohydrolysis biomass was obtained from pretreatment process with four different raw material, which are mixed rice biomass, rice husk, rice straw and empty fruit bunch (EFB). The two main component from the pretreatment that need to eradicate P.canaliculata are furfural and phenol. Pretreatment of mixed rice biomass at 190 produced 39.5% (w/v) of furfural and 1.18% (w/v) of phenol which could eradicate the snail. The biomass steam condensate to eradicate species of P.canaliculata eggs are successful penetrated through the eggshell (protein layer) and disrupt further hatching development.